Why eat fish? Factors influencing seafood consumer choices in British Columbia, Canada. (15th July 2017) - Murray, Grant; Wolff, Kelsey; Patterson, Michele
Highlights: Article characterizes the relative importance of multiple factors affecting seafood consumption choices. Sensory attributes of seafood (taste, smell, and appearance) are the most important factors. Product provenance (local/non-local; wild/farm-raised) is very important for a portion of respondents, but not others. The perceived sustainability of the product is of relatively low importance.